Visual vs. Spatial Contributions to Microsaccades and Visual-Spatial Working Memory (Journal of Eye Movement Research, 2014)
Microsaccade rates and directions were monitored while observers performed a visual working memory task at varying retinal eccentricities. We show that microsaccades generate no interference in a working memory task, indicating that spatial working memory is at least partially insulated from oculomotor activity. Intervening tasks during the memory interval affected microsaccade patterns; microsaccade frequency was consistently higher during concurrent spatial tapping (no visual component) than during exposure to dynamic visual noise (no task). Average microsaccade rate peaked after appearance of a fixation cross at the start of a trial, and dipped at cue onset and offset, consistent with previous results. Direction of stimuli in choice tasks did not influence microsaccade direction,however.